A conceptual framework for identifying key employee branding dimensions: A study of hospitality industry - Praveen Dhiman; Sangeeta Arora (Journal of Innovation & Knowledge (JIK), 2020)
The current research adds to the employee branding literature by building a conceptual framework to identify key employee branding dimensions in the context of the Indian hospitality industry that has been overlooked by the previous literature. A survey-based approach is employed on a sample of 421 customer-contact employees of the top ten luxury chain hotels, operating in five major tourist destinations of Northern India. The main thrust of the study is to gauge employees' perspectives concerning internal and external brand management efforts pursued by luxury chain hotels. Thus, a conceptual model was designed and tested through confirmatory factor analysis using Analysis of Moment Structures (AMOS v. 20). After reviewing the extant literature and conducting an empirical investigation, the study validates employee branding as a five-dimensional first-order reflective construct namely perceived brand-centred human resource management, perceived internal brand communication, perceived brand-specific transformational leadership, perceived brand-oriented support and perceived external brand prestige. The paper concludes with discussion, implications, provides limitations and directions for further research.
Keywords: L; L08; L83; 650; Customer-contact employees; Employee branding dimensions; Luxury chain hotels; Northern India